Intrinsic Hippocampal Excitability Changes of Opposite Signs and Different Origins in CA1 and CA3 Pyramidal Neurons Underlie Aging-Related Cognitive Deficits - Oh, M. Matthew; Simkin, Dina; Disterhoft, John F. (Frontiers in Systems Neuroscience, 2016)
Aging-related cognitive deficits have been attributed to dysfunction of neurons due to failures at synaptic or intrinsic loci, or both. Given the importance of the hippocampus for successful encoding of memory and that the main output of the hippocampus is via the CA1 pyramidal neurons, much of the research has been focused on identifying the aging-related changes of these CA1 pyramidal neurons. We and others have discovered that the postburst afterhyperpolarization (AHP) following a train of action potentials is greatly enlarged in CA1 pyramidal neurons of aged animals. This enlarged postburst AHP is a significant factor in reducing the intrinsic excitability of these neurons, and thus limiting their activity in the neural network during learning. Based on these data, it has largely been thought that aging-related cognitive deficits are attributable to reduced activity of pyramidal neurons. However, recent in vivo and ex vivo studies provide compelling evidence that aging-related deficits could also be due to a converse change in CA3 pyramidal neurons, which show increased activity with aging. In this review, we will incorporate these recent findings and posit that an interdependent dynamic dysfunctional change occurs within the hippocampal network, largely due to altered intrinsic excitability in CA1 and CA3 hippocampal pyramidal neurons, which ultimately leads to the aging-related cognitive deficits.